2016
DOI: 10.1097/mlr.0000000000000583
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination and Delayed Health Care Among Transgender Women and Men

Abstract: Transgender patients who need to teach their providers about transgender people are significantly more likely to postpone or not seek needed care. Systemic changes in provider education and training, along with health care system adaptations to ensure appropriate, safe, and respectful care, are necessary to close the knowledge and treatment gaps and prevent delayed care with its ensuing long-term health implications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
142
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 290 publications
(153 citation statements)
references
References 21 publications
6
142
1
4
Order By: Relevance
“…In another study, African American sexual minority women who attributed their negative experiences in a healthcare setting to multifactorial discrimination decreased their health care utilization following the negative experience [54]. Among minority populations, discrimination during health care is significantly associated with delayed care and stopped treatment [55, 56]. Disengagement with the health care system due to negative patient-provider interactions, resulting from discrimination, may partially explain poor health outcomes across marginalized communities [5759].…”
Section: Discussionmentioning
confidence: 99%
“…In another study, African American sexual minority women who attributed their negative experiences in a healthcare setting to multifactorial discrimination decreased their health care utilization following the negative experience [54]. Among minority populations, discrimination during health care is significantly associated with delayed care and stopped treatment [55, 56]. Disengagement with the health care system due to negative patient-provider interactions, resulting from discrimination, may partially explain poor health outcomes across marginalized communities [5759].…”
Section: Discussionmentioning
confidence: 99%
“…Access to health care is influenced by gender identity; differences exist between transgender subgroups in their experience of health care access barriers and health care utilization (Gonzales & Henning-Smith, 2017). For example, studies have revealed that trans men have a greater tendency than trans women to delay health care due to the fear of discrimination (Cruz, 2014;Jaffee, Shires, & Stroumsa, 2016). Furthermore, researchers have identified the increased disadvantages of transgender individuals who belong to more than one marginalized community (e.g., ethnic/racial minority, low income and visually non-conforming), as these individuals experience even more prevalent discrimination and substandard care (Bradford et al, 2013;Grant et al, 2011;Jaffee et al, 2016;Kattari, Walls, Whitfield, & Langenderfer-Magruder, 2015Lambda Legal, 2010;Shires & Jaffee 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Across numerous studies of transgender women, discrimination in accessing healthcare services has been linked to healthcare delay and avoidance and overall worse health outcomes, including lack of preventative healthcare (5253). While the aforementioned increase in access to healthcare insurance in Study 2 was a promising finding, the concurrent higher prevalence of reported healthcare discrimination, as well as the decrease in gender-related surgeries, with the exception of genital reconstruction (i.e., vaginoplasty), highlighted the continued need for transgender-specific clinical and cultural competency trainings for healthcare providers.…”
Section: Discussionmentioning
confidence: 99%